Ljubelj kot zadnje nemško oporišče na Gorenjskem med drugo svetovno vojno - Kocjančič, Klemen (Kronika (Ljubljana), 2020)
The article presents the history of the Ljubelj labour-concentration camp as well as the importance of the mountain pass and the road tunnel constructed during the Second World War. In the second half of the war, the internees and civilian labourers on both sides of the Slovenian' Austrian border constructed the road tunnel, which was only used during the mass retreat of the German and collaborationist forces from Slovenia towards Austria. To ensure a safe retreat for several thousands of persons crossing the mountain pass and the tunnel, the German and collaborationist forces mounted a fierce defence of access routes to Ljubelj. For this reason, the Partisan forces could only liberate the area several days after the official capitulation of the Third Reich
Keywords: Concentration camps; delovna taborišča; Druga svetovna vojna; Gradnja; Koncentracijska taborišča; Ljubelj; Mauthausen; nemška oporišča; nemška vojska; taborišča; World war II